2012
DOI: 10.1021/es3001294
|View full text |Cite
|
Sign up to set email alerts
|

Combined Sewer Overflows: An Environmental Source of Hormones and Wastewater Micropollutants

Abstract: Data were collected at a wastewater treatment plant (WWTP) in Burlington, Vermont, USA, (serving 30,000 people) to assess the relative contribution of CSO (combined sewer overflow) bypass flows and treated wastewater effluent to the load of steroid hormones and other wastewater micropollutants (WMPs) from a WWTP to a lake. Flow-weighted composite samples were collected over a 13 month period at this WWTP from CSO bypass flows or plant influent flows (n = 28) and treated effluent discharges (n = 22). Although C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(138 citation statements)
references
References 56 publications
5
131
1
1
Order By: Relevance
“…For all of the treatments, dialysis bags were filled with 100 ml of Mississippi River water and 100 ml of primary sewage effluent from a local wastewater treatment plant (City of Davenport Water Pollution Control Plant; GPS coordinates 41°29=31.83ЉN and 90°37=41.71ЉW). A 1:1 ratio was selected to mimic sewage spills such as CSO events, where estimated loads from sanitary sewage can be greater than 50% and pollutants such as fecal indicator organisms are reported to be up to 10 times higher than in treated sewage discharges (35)(36)(37)(38)(39)(40), and is consistent with earlier decay studies (23-25, 34, 41, 42). Both river water and primary sewage effluent were collected in the morning on the same day that the mesocosm was deployed.…”
Section: Methodsmentioning
confidence: 57%
“…For all of the treatments, dialysis bags were filled with 100 ml of Mississippi River water and 100 ml of primary sewage effluent from a local wastewater treatment plant (City of Davenport Water Pollution Control Plant; GPS coordinates 41°29=31.83ЉN and 90°37=41.71ЉW). A 1:1 ratio was selected to mimic sewage spills such as CSO events, where estimated loads from sanitary sewage can be greater than 50% and pollutants such as fecal indicator organisms are reported to be up to 10 times higher than in treated sewage discharges (35)(36)(37)(38)(39)(40), and is consistent with earlier decay studies (23-25, 34, 41, 42). Both river water and primary sewage effluent were collected in the morning on the same day that the mesocosm was deployed.…”
Section: Methodsmentioning
confidence: 57%
“…Rainfall may be one of the causes associated with this phenomenon (Ternes 1998;Tauxe-Wuersch et al 2005;Vieno et al 2007;Phillips et al 2012;Ryu et al 2014). That was the reason why many studies emphasized that sampling campaigns were conducted avoiding rainfall (Kosma et al 2010;Baker and Kasprzyk-Hordern 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Seoul, South Korea, the occurrence and removal of 29 endocrinedisrupting chemicals (EDCs) and PPCPs in the wastewaters under both dry and wet weather conditions were investigated, and the influence of rainfall was also found to be evident (Ryu et al 2014). Recently, combined sewer overflows (CSOs), caused by heavy rain or snowmelt, has been identified as an environmental source of hormones and micropollutants, as the mixture of raw wastewater and stormwater can overload the capacity of WWTPs, resulting in the discharge of untreated wastewater and subsequently deteriorated quality of the receiving surface water (Weyrauch et al 2010;Phillips et al 2012;Madoux-Humery et al 2013). Phillips et al (2012) found that annual loads of trace contaminants, which could be removed by >95 % in the WWTPs, were dominated by CSO.…”
Section: Introductionmentioning
confidence: 99%
“…Their suitability as chemical markers [12,13] and their fate [14,15] were investigated. In addition, the concentration of PPCPs in CSOs itself has been reported in several studies [16][17][18]. However, only a limited number of investigations have been undertaken on CSO pollution in receiving waters, especially in coastal environments.…”
Section: Introductionmentioning
confidence: 98%